Enhancing off-season fertility in dairy buffaloes through monensin supplementation - BRAR, P S; NANDA, A S; HONPARKHE, M; SINGH, H (The Indian Journal of Animal Sciences, 2013)
Ninety suboestrus, pluriparous, Murrah buffaloes (60–180 days post-partum) reared under semi-intensive systemformed the subject of this study. These buffaloes failed to exhibit overt oestrus and remained un-bred. The buffaloeswere subjected to synchronized breeding using modified ovsynch protocol which included 5 ml receptal (20 μg buserelin) on day 0, 2 ml vetmate (500μg cloprostenol) on day 7 and 2.5 ml receptal (60 h after cloprostenol) on day 9, injected intramuscularly. Fixed time AI was done at 16 and 40 h after the last injection. Some of the buffaloes which returned to oestrus about 15–21 days later were served naturally. The pregnancy was diagnosed 90 days later through rectal palpation of genitalia. In the first phase, buffaloes were synchronized and bred either in the favourable breeding season (October through March; n= 40) or in the unfavorable season (April through July; n=40). The first service and the overall conception rates were 30 and 37.5% (during unfavourable season) and 55 and 65% (during favourable season; P